Diversity of Parallel Guanine Quadruplexes Induced by Guanine Substitutions - Bednářová, Klára; Vorlíčková, Michaela; Renčiuk, Daniel (International journal of molecular sciences, 2020)
Recently, we reported an inhibitory effect of guanine substitutions on the conformational switch from antiparallel to parallel quadruplexes (G4) induced by dehydrating agents. As a possible cause, we proposed a difference in the sensitivity of parallel and antiparallel quadruplexes to the guanine substitutions in the resulting thermodynamic stability. Reports on the influence of guanine substitutions on the biophysical properties of intramolecular parallel quadruplexes are rare. Moreover, such reports are often complicated by the multimerisation tendencies of parallel quadruplexes. To address this incomplete knowledge, we employed circular dichroism spectroscopy (CD), both as stopped-flow-assisted fast kinetics measurements and end-point measurements, accompanied by thermodynamic analyses, based on UV absorption melting profiles, and electrophoretic methods. We showed that parallel quadruplexes are significantly more sensitive towards guanine substitutions than antiparallel ones. Furthermore, guanine-substituted variants, which in principle might correspond to native genomic sequences, distinctly differ in their biophysical properties, indicating that the four guanines in each tetrad of parallel quadruplexes are not equal. In addition, we were able to distinguish by CD an intramolecular G4 from intermolecular ones resulting from multimerisation mediated by terminal tetrad association, but not from intermolecular G4s formed due to inter-strand Hoogsteen hydrogen bond formation. In conclusion, our study indicates significant variability in parallel quadruplex structures, otherwise disregarded without detailed experimental analysis.
Keywords: termodynamika; vodíková vazba; konformace nukleové kyseliny; Models, Molecular; cirkulární dichroismus; Nucleic Acid Conformation; guanin; parallel guanine quadruplex; Guanine; DNA; Amino Acid Substitution; substituce aminokyselin; Hydrogen Bonding; Thermodynamics; DNA secondary structure; molekulární modely; G-kvadruplexy; Circular Dichroism; multimerisation; G-Quadruplexes; circular dichroism; stopped-flow